One-Dimensional Simulation of the In-Situ Oil Combustion with Consideration to Fluid and Solid Combustible Components - I. A. Koznacheev; K. V. Dobrego (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2019)
The one-dimensional axisymmetric problem of initiation of a combustion wave in an oil-saturated reservoir is solved numerically. Two combustible components, viz. liquid (oil) and solid (kerogen, oil sorbate) were considered. The influence of the abovementioned components on time of the hot site ignition and combustion front speed was simulated and analyzed. It was demonstrated that growth of the mass fraction of liquid component (the total heat content being preserved) results in retard of formation of the hot site near the well and in reduction of the maximum temperature of the combustion wave, disregarding of the higher reactivity of liquid combustible. Simulation revealed existence of the two “peaks” of thermal front velocity. The first one corresponds by time to ignition of combustion site. The second one corresponds to a moment when the solid component combustion front overrides the oil displacement front. Calculations shown, that thermal wave propagation velocity, at least after passing the “peaks” and transition to quasi-steady regime, does not considerably depend on mass traction of the fluid component in the system. A typical term of the exothermic reaction site formation may increase from 50 to 200 days in case of growth of the liquid component content from 30 to 80 mass % at the considered thermal conditions in the oil reservoir. Thus, the implementation of the thermo-gas method in high-productive layers increases the likelihood of difficulty of initiation of a fire. Therefore, the study of the regularities of intra-combustion in such cases is of a particular interest. For instance, the task of combustion site ignition may be resolved by increase of oxygen content in blowing-gas or by means of non-steady (periodical) blowing. It is found that taking into consideration of highly reactive liquid component results in widening (diffusion) of the thermal front, which may play positive role in its spatial thermo-hydrodynamic stabilization. The results of simulation may be utilized for development of technical projects of oil recovery via in-situ combustion, for designing of furnaces utilizing multicomponent fixed layer fuels and for thermochemical investigation of multicomponent fuels.